Knowing in Practice: Enacting a Collective Capability in Distributed Organizing - Orlikowski, Wanda J. (Organization Science, 2002)
In this paper, I outline a perspective on knowing in practice which highlights the essential role of human action in knowing how to get things done in complex organizational work. The perspective suggests that knowing is not a static embedded capability or stable disposition of actors, but rather an ongoing social accomplishment, constituted and reconstituted as actors engage the world in practice. In interpreting the findings of an empirical study conducted in a geographically dispersed hightech organization, I suggest that the competence to do global product development is both collective and distributed, grounded in the everyday practices of organizational members. I conclude by discussing some of the research implications of a perspective on organizational knowing in practice.